Biorelevant dissolution of candesartan cilexetil - Lucie Gruberová; Bohumil Kratochvil (International Association of Physical Chemists (IAPC), 2017)
The choice of an appropriate medium for dissolution tests is an essential step during a dosage form development. The adequate design of dissolution testing enables forecasting in vivo behavior of drug formulation. Biorelevant media were developed for this purpose because dissolution media described in the International Pharmacopoeia are not thoroughly suitable. Therefore, we carried out solubility and dissolution tests in biorelevant media and we compared the results with data measured in compendial dissolution media. A shake-flask method and standard paddle apparatus were used. The concentration was measured by a UV-Vis spectrophotometer. An oral solid dosage form with poorly soluble drug candesartan cilexetil was tested. Significant differences in the solubility and dissolution profiles of candesartan cilexetil were observed. The study offers the overview of compendial and biorelevant media simulating fasted state that can be analyzed by a spectrophotometric technique.